An initial genetic analysis of gemcitabine-induced high-grade neutropenia in pancreatic cancer patients in CALGB 80303 (Alliance). Issue 6 (August 2019) - Innocenti, Federico; Jiang, Chen; Sibley, Alexander B.; Denning, Stefanie; Etheridge, Amy S.; Watson, Dorothy; Niedzwiecki, Donna; Hatch, Ace J.; Hurwitz, Herbert I.; Nixon, Andrew B.; Furukawa, Yoichi; Kubo, Michiaki; et al.
Abstract : Objectives: One of the standard of care regimens for advanced pancreatic cancer is gemcitabine-based chemotherapy. The efficacy of gemcitabine is limited by dose-limiting hematologic toxicities especially neutropenia. Uncovering the variability of these toxicities attributed to germline DNA variation is of great importance. Patients and methods: CALGB 80303 was a randomized study in advanced pancreatic cancer patients treated with gemcitabine with or without bevacizumab. The study protocol included genotyping of genes of gemcitabine disposition ( CDA, DCTD, SLC29A1, SLC28A1, and SLC29A2 ), as well as a genome-wide analysis. The clinical phenotype was time to early high-grade neutropenia event accounting for progression or death or other treatment-terminating adverse events as competing for informative events. The inference was carried out on the basis of the association between genotype and cause-specific hazard of a neutropenic event. Results: The primary analyses were carried out on the basis of 294 genetically estimated European pancreatic cancer patients. For CDA rs2072671 (A>C), AC and CC patients had a lower risk of neutropenia than AA patients ( P =0.01, hazard ratio: 0.61, 95% confidence interval: 0.41–0.89). For SLC28A1 rs3825876 (G>A), AA patients have a higher risk of neutropenia than GA and GG patients ( P =0.02, hazard ratio: 1.51, 95% confidence interval: 1.06–2.16). CDA rs2072671 was associated with increased mRNA expression in whole blood in three studies ( P =2.7e−14, 6.61e−62, and 9.70e−65). In the genome-wide analysis, variants in TGFB2 were among the top hits (lowest P =1.62e−06) but had no effect in luciferase assays. Conclusion: This is the first genetic analysis of gemcitabine-induced neutropenia using a competing risk model in a prospective randomized clinical study has proposed a potentially novel mechanism of the protective effect of the CDA rs2072671 variant. Further confirmation is needed. Abstract : Supplemental Digital Content is available in the text.